Effect of Dexamethasone on Tail Regeneration in the Electric Black Ghost Knifefish Apteronotus albifrons (Linnaeus, 1766) - Ammar A. Issa; Ilham J. J. Alshami; Hutheyfa A. H. Al-Salih (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2023)
The study was conducted to find out the impact of dexamethasone of different doses on tail regeneration in the electric black ghost knifefish Apteronotus albifrons (Linnaeus, 1766) after two weeks of amputation. Fish were distributed into five equal groups; Dexamethasone drug was applied at concentrations of 0, 1, 2, 3 and 4 mg.l-1. Water was exchanging every 48 hours with new prepared drug to ensure its stability in treatments. Concentrations 1, 2 and 3 mg.l-1 were not lethal , while the concentration 4 mg.l-1 was lethal, It was observed that fish were dead  after four days for concentration 4 mg.l-1.The study showed that the group of control was increased considerably (P < 0.05) (4.5mm± 0.866) in the tail after 14 days of amputation in comparing with treated groups. Treated groups (1, 2 and 3 mg.l-1) showed slowly increase with an average 2.83mm ±0.763, 2.50mm ±0.500, and 2.33mm ±0.577 respectively. The mean of relative gene expression of the junb was 1.109 in control group that is significant (P < 0.05) compared with treated groups that showed a decrease in junb expression (0.074 for 1 mg.l-1, 0.050 for 2 mg.l-1 and 0.006 for 3 mg.l-1). Current study concludes that dexamethasone inhibit tissues regeneration after amputation via suppress stem cells growth, and junb gene specific for stem cells enhancing and the drug reduced its expression.